2010
DOI: 10.1186/1471-2164-11-450
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the sialotranscriptome of the brown dog tick, Rhipicephalus sanguineus

Abstract: BackgroundRhipicephalus sanguineus, known as the brown dog tick, is a common ectoparasite of domestic dogs and can be found worldwide. R.sanguineus is recognized as the primary vector of the etiological agent of canine monocytic ehrlichiosis and canine babesiosis. Here we present the first description of a R. sanguineus salivary gland transcriptome by the production and analysis of 2,034 expressed sequence tags (EST) from two cDNA libraries, one consctructed using mRNA from dissected salivary glands from femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 110 publications
2
72
0
7
Order By: Relevance
“…Similar to other studies in salivary glands, we identified putative glycine-rich (GGY) cuticlerelated (CV437645) and cement (Contig 2328) proteins that may be involved in structural interactions of the peritrophic matrix between the cuticle and salivary gland tissues, in addition to cement cone 13 formation during attachment (Francischetti et al, 2010;Maruyama et al, 2010), as well as putative mucins (CV452616 and CV444691) (Francischetti et al, 2010). A vaccination trial using a mucin isolated from female R. microplus homogenates could not demonstrate greater protection against infestation compared with that of Bm86 (McKenna et al, 1998).…”
Section: Structural Proteins Signal Transduction and Other Proteinssupporting
confidence: 61%
See 1 more Smart Citation
“…Similar to other studies in salivary glands, we identified putative glycine-rich (GGY) cuticlerelated (CV437645) and cement (Contig 2328) proteins that may be involved in structural interactions of the peritrophic matrix between the cuticle and salivary gland tissues, in addition to cement cone 13 formation during attachment (Francischetti et al, 2010;Maruyama et al, 2010), as well as putative mucins (CV452616 and CV444691) (Francischetti et al, 2010). A vaccination trial using a mucin isolated from female R. microplus homogenates could not demonstrate greater protection against infestation compared with that of Bm86 (McKenna et al, 1998).…”
Section: Structural Proteins Signal Transduction and Other Proteinssupporting
confidence: 61%
“…Other protease inhibitors related to the thyroglobulin type-1 repeat containing proteins or thyropins (Contig 300) and the alpha-2-macroglobulin family (Contig 2131 and Contig 1745) were identified. Thyropins have been proposed to act as inhibitors of cysteine proteases, as well as binding partners for heparin (Anatriello et al, 2010;Francischetti et al, 2010). Alpha-2-macroglobulins are universal protease inhibitors involved in clearance of exogenous proteases and innate immunity.…”
Section: Defense Mechanisms and Blood Meal Acquisitionmentioning
confidence: 99%
“…(3) A molécula AFXa se liga ao fator X ativo e a molécula AaTI se liga à trombina impedindo a coagulação sanguínea. (ANATRIELLO et al, 2010;GARCIA et al, 2014;RIBEIRO et al, 2011;VALENZUELA et al, 2002a). aegypti, a literatura a respeito deste assunto ainda é escassa e pouco se sabe sobre as moléculas responsáveis por tais atividades.…”
Section: Figura 2-representação Esquemática Das Ações Anti-hemostáticunclassified
“…A fixação ocorre por meio das peças bucais aproximadamente uma hora após alcançar o hospedeiro. As glândulas salivares começam a secretar um material acelular viscoso que envolve as peças bucais formando um cone de cimento que fixa o carrapato na pele do hospedeiro (de Campos Pereira et al, 2008, Anatriello et al, 2010.…”
Section: Fase Parasitáriaunclassified
“…Dentre as secreções salivares das larvas encontram-se substâncias farmacologicamente ativas com propriedades imunossupresoras, anti-inflamatórias, vasodilatadoras e anti-hemostáticas que permitem evadir o sistema imune do bovino e impedir a coagulação sanguínea favorecendo a alimentação do carrapato (Valenzuela, 2004, de Campos Pereira et al, 2008, Anatriello et al, 2010.…”
Section: Fase Parasitáriaunclassified